Polanyi and Schumpeter: Transitional Processes via Societal Spheres - Theresa Hager; Ines Heck; Johanna Rath (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2022)
We examine parallels and differences, intersections and complementarities in the notions of societal transition by Karl Polanyi and Joseph A. Schumpeter. Considering their intellectual heritage, methodology and scope, we propose a three-sphere framework to analyse their theories and study the interdependencies within capitalism. The three spheres essential to both thinkers are the political, the socio-cultural and the economic: the latter dominates the others in capitalist societies. The resulting rationalisation (Schumpeter) and commodification (Polanyi) distort the socio-cultural sphere and transcend towards the political sphere which undermines democracy. Applying our framework, we identify similar transitional mechanisms but derive different implications for society.
Keywords: B25; 330; Karl Polanyi; Joseph A. Schumpeter; transformation; institutional change